Audio Steganography Using Modified Enhanced Least Significant Bit In 802.11n - Carolus Ferdy Setiaji Hartoko; Suhartono Tjondronegoro; Bambang Hidayat (eProceedings of Engineering, 2015)
Steganography  is  a  technique  to  improve  the  security  of  data,  which  is  by  inserting  messages  or confidential information using a medium called the host or carrier or cover. A wide variety of digital media can be  used  as  a  host,  among  others  audio,  image,  video,  text,  header,  IP  datagram,  and  so  forth.  For  audio steganography,  the embedded audio is called stego-audio.  Steganography  can be cracked by using steganalysis. By exploiting the weaknesses  of each steganography method. Many steganography method has been developed to increase its performance. This work proposed audio steganography scheme called MELSB which is modified version of ELSB. This method use Modified Bit Selection Rule to increase SNR and robustness of stego-audio. SNR result after applying MELSB scheme is increased. MELSB scheme also increase robustness of stego-audio. MELSB still work fine until amplification  level 1.07. MELSB also work fine against noise addition better than ELSB and LSB. It give BER and CER with value 0 at SNR 33 dB.  MELSB work fine in real-time condition on 802.11n WLAN if there is no transcoding and noise addition between sender’s and recipient’s computer